2004
DOI: 10.1080/00016470410004094
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic orientation and assessment of hip dysplasia in adults

Abstract: BackgroundThe study was performed to qualify the source material of 4 151 pelvic radiographs for the research into the relationship between unrecognised childhood hip disorders and the development of hip osteoarthrosis, and to investigate the effect of varying degrees of pelvic tilt and rotation on the measurements of radiographic indices of hip dysplasia.Material and methods We investigated the effect of varying pelvic orientation on radiographic measurements of acetabular dysplasia using a cadaver model. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…Except for Tönnis angle, as the pelvis tilted anteriorly toward or posteriorly away from the beam, the acetabular parameters showed increased or decreased acetabular coverage, respectively. Consistent with our findings from a cadaver with varying abnormal morphologic features of the pincer, Jacobsen et al [14] found rotation and tilt affected lateral center-edge angle and Sharp angle in two cadavers with normal morphologic features of the hip. Siebenrock et al [26] found an anterior tilt of 9°and rotation of 6°away from the x-ray beam produced a crossover sign in every pelvis.…”
Section: Discussionsupporting
confidence: 91%
“…Except for Tönnis angle, as the pelvis tilted anteriorly toward or posteriorly away from the beam, the acetabular parameters showed increased or decreased acetabular coverage, respectively. Consistent with our findings from a cadaver with varying abnormal morphologic features of the pincer, Jacobsen et al [14] found rotation and tilt affected lateral center-edge angle and Sharp angle in two cadavers with normal morphologic features of the hip. Siebenrock et al [26] found an anterior tilt of 9°and rotation of 6°away from the x-ray beam produced a crossover sign in every pelvis.…”
Section: Discussionsupporting
confidence: 91%
“…Accurate assessment of acetabular version and anterior and posterior femoral head coverage can be difficult, and changes in patient positioning can lead to errors in measurement [4,24,45,48]. Two-dimensional CT studies have become an integral part of diagnosis and preoperative planning, especially when assessing deficiencies in the transverse plane [5,26,29,33,41,59].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous cadaver study we found that extreme pelvic rotation and inclination/reclination had significant influence on hip dysplasia assessment [12]. To stay inside ±3°of error of measurements of the CE angle, FOI inclusion limits of 0.7-1.8 were applied to radiographs.…”
Section: Exclusion Of Radiographsmentioning
confidence: 99%